2018
DOI: 10.1002/jcp.27124
|View full text |Cite
|
Sign up to set email alerts
|

DUSP1 recuses diabetic nephropathy via repressing JNK‐Mff‐mitochondrial fission pathways

Abstract: Excessive mitochondrial fission has been identified as the pathogenesis of diabetic nephropathy (DN), although the upstream regulatory signal for mitochondrial fission activation in the setting of DN remains unknown. In the current study, we found that dual-specificity protein phosphatase-1 (DUSP1) was actually downregulated by chronic hyperglycemia stimulus. Lower DUSP1 expression was associated with glucose metabolism disorder, renal dysfunction, kidney hypertrophy, renal fibrosis, and glomerular apoptosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 67 publications
1
58
0
Order By: Relevance
“…However, how Sirt1 regulates mitochondrial fission in HG-induced endothelial injury remains to be fully elucidated. It has been reported that the JNK pathway is involved in the regulation of mitochondrial fission (28,40,47). In addition, previous studies have confirmed the association between Sirt1 and the JNK pathway (48-50).…”
Section: Discussionmentioning
confidence: 99%
“…However, how Sirt1 regulates mitochondrial fission in HG-induced endothelial injury remains to be fully elucidated. It has been reported that the JNK pathway is involved in the regulation of mitochondrial fission (28,40,47). In addition, previous studies have confirmed the association between Sirt1 and the JNK pathway (48-50).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that mitochondrial fission is primarily modulated by the JNK pathway. For example, in tongue cancer, cell viability is determined by mitochondrial fission, which is highly affected by the JNK-Fis1 biological axis , and in diabetic nephropathy, hyperglycemia-mediated renal injury is regulated by the JNK-MFF-mitochondrial fission pathway (Sheng et al 2019). In addition, in postinfarction cardiac injury, the JNK-Drp1 pathway is the upstream mediator of mitochondrial fission and participates in the management of cardiomyocyte death and myocardial fibrosis (Wang and Song 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Impaired mitophagy is involved in the development and progression of fatty liver disease via promoting hepatocyte death Zhou et al 2018a). Moreover, the pathogenesis of diabetic nephropathy has been linked to excessive mitochondrial fission (Sheng et al 2018).…”
Section: Introductionmentioning
confidence: 99%